Դավիթ Բեկի գլխավորած Սյունիքի ազատագրական պայքարի ներկայացումը հայ կինոարվեստում - Շահբազյան, Արմինե (Հայաստանի պատմության թանգարան)
The objectives of this article are to present the creative and organizational work carried out by directors, creative team and actors during the filming of "David Bek" and "Hope Star", the difficulties encountered and their overcoming. The aim of the article is to analyze the collected materials, present the history of the creation of films and emphasize their historical significance in the life of the Armenian people. Both films were shot under the influence of different events and showed that if the goal was to turn to the heroic past of one's own people, no obstacles could interfere. These films once again reminded people that we had a victorious past and we must remember our heroes. The patriotic image of David Bek is of great value in shaping the patriotic views of generations. Задачи данной статьи – представить творческую и организационную работу, проделанную режиссерами, творческими группами и актерами во время съемок фильмов “Давит Бек” и “Звезда надежды", возникшие трудности и их преодоление. Цель статьи – проанализировав собранные материалы, представить историю создания фильмов и подчеркнуть их историческое значение в жизни армянского народа. Оба фильма были сняты под влиянием разных событий и показали, что если ставится цель обратиться к героическому прошлому собственного народа, то никакие препятствия не могут помешать. Эти фильмы еще раз напомнили публике, что у нас было победоносное прошлое, и мы должны помнить наших героев. Образ Давита Бека своим патриотизмом имеет большую ценность в формировании патриотических взглядов поколений.
Keywords: Մշակութային մարդաբանություն